The Central Role of Imagination in Linguistics, Philosophy and Logic - Itkonen, Esa (Public Journal of Semiotics, 2019)
Imagination is often accused of being “vulnerable”, or even downright unrealizable as a source of knowledge. I argue that this is mistaken, at least for some kinds of systematic imagination. First, imagination is shown to be key for the notion of entailment, which is central in philosophical and linguistic semantics, and in logic. Further, I show how such a non-psychological notion of imagination vindicates so-called “Objectivism”, attacked in cognitive linguistics. There are indeed limits to imagination, related to contradiction and ontological puzzles, but once handled with care, such limits do not invalidate it either. In sum, despite scepticism about imagination from Aristotle to the present, I show that it is if fact inevitable, intimately linked with normativity and rationality.